1999
DOI: 10.1021/bi982381n
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Subunit−Subunit Contact Surfaces on the β Subunit of Escherichia coli RNA Polymerase

Abstract: The RNA polymerase core enzyme of Escherichia coli is composed of 2alpha, 1beta, and 1beta' subunits. Previously we mapped the alpha-alpha, alpha-beta, and alpha-beta' contact sites on the alpha subunit. Here we analyzed the alpha subunit contact sites on the beta subunit by using various experimental approaches: (i) comparison of the proteolytic cleavage map between the unassembled free beta subunit and the alpha2 beta complex; (ii) analysis of the binary complex formation between His6-tagged intact alpha sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…18). However, similar analysis performed by the Ishihama group (19) suggested that the primary determinants of ␣ binding include conserved segments F and G, corresponding to E. coli ␤ amino acids 800 -900.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…18). However, similar analysis performed by the Ishihama group (19) suggested that the primary determinants of ␣ binding include conserved segments F and G, corresponding to E. coli ␤ amino acids 800 -900.…”
mentioning
confidence: 69%
“…Moreover, ␤ 950 -1342 interacted with His 6 -␣ WT and His 6 -␣ R45A in vitro with the same (low) efficiency (18). On the other hand, Nomura et al (19) mapped the primary ␣-binding site to ␤ amino acids 737-904. We constructed pPC86-based two-hybrid plasmids with ␤ 800 -911 (conserved segments F and G), and ␤ 907-1231 , (conserved segments H and a small portion of I) and tested them for their ability to interact with ␣.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Note that G1228D alone and in combination with six other primary mutations, but not with M1273V, with which it was initially isolated, also prevents assembly (Malik et al, manuscript in preparation).] Indeed, a recent study defines an assembly determinant for the ␣ subunit in the conserved ␤ region encompassing residues 907→1246 (and the extreme C-terminus of ␤ has been implicated in ␤ 0 association; Wang et al 1997; but see also Nomura et al 1999). Second, two of the three assembled enzymes are functional in vitro and do not blockade (cluster #1, G1228D (M1273V) and L1238P (G1271V)) whilst the two primary mutants, M1273V and G1271V, are both transcriptionally proficient and inhibitory in vitro.…”
Section: In Vivomentioning
confidence: 99%
“…В работах [22,8] показано, что за-мены в ТАТА-боксе промотора SV40 (ТАТАААА→ТАТТТАТ и ТАТАААА→ ТАТАСА) вызывают снижение сродства дрожжевого ТВР к ДНК примерно в 4 раза, нуклеотидная замена в ТАТА-боксе промотора гена hsp70 (ТАТА→ TGTA) приводит к снижению уровня транскрипции примерно в 10 раз, а аналогичные замены в промоторе гена his3 (TATA→TGTA и TATA→TATG) снижают уровень транскрипции почти в 100 раз. Wobbe и Struhl [34] пока-зали, что мутации в консенсусе Т 1 А 2 Т 3 А 4 А 5 А 6 А 7 , функционирование которого анализировали в контексте двадцати пяти промоторов, поразному снижали активность промотора.…”
unclassified